2021
DOI: 10.3991/ijet.v16i17.25337
|View full text |Cite
|
Sign up to set email alerts
|

Use of Virtual Reality Technology in Animation Course Teaching

Abstract: With the rapid development of Internet technology, in consequence of the outbreak of COVID-19, colleges and universities have postponed the start of term, in order to protect the life safety of teachers and students. However, to avoid affecting students’ academic studies, colleges and universities have taken various virtual reality technologies to implement personalized online teaching on students. However, there are still some problems in actual teaching, such as the monotonous teaching mode of animation cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Moreover, the production of high-caliber VR content demands robust hardware and advanced programming skills, which could pose a barrier to its accessibility. 45…”
Section: Virtual Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the production of high-caliber VR content demands robust hardware and advanced programming skills, which could pose a barrier to its accessibility. 45…”
Section: Virtual Realitymentioning
confidence: 99%
“…There's also the potential for viewer discomfort due to factors such as motion sickness. Moreover, the production of high‐caliber VR content demands robust hardware and advanced programming skills, which could pose a barrier to its accessibility 45 …”
Section: Impact Of New Technologies On Animationmentioning
confidence: 99%
“…For example, some science and engineering disciplines in Colleges and universities will carry out metal smelting teaching practice activities, but there are often problems such as scarce resources and high risk of field teaching. Teachers can make students familiar with the environment and learning tasks in advance by using virtual reality technology, and can also let students who do not have practical conditions experience the whole process of practice through virtual reality technology to improve students' professional level [9].…”
Section: Application Of Virtual Reality Technology In Teachingmentioning
confidence: 99%
“…It indicated that VR technology can be beneficial to improve language learning as an educational resource. Other researchers showed different frameworks of using VR in teaching [10]- [12]. Also, some research was conducted in Palestine showed interest in integrating VR in educational domain.…”
Section: Literature Reviewmentioning
confidence: 99%